Robotic Management of Endometriosis: Discussion of Use, Criteria and Advantages: a Review of the Literature - Ioannis D. Gkegkes; Christos Iavazzo; George Iatrakis; Paraskevi-Evangelia Iavazzo; Fani Pechlivani; Evangelia Antoniou; Konstadia Bakalianou (Acta Medica, 2020)
Endometriosis is a very common benign condition affecting fertility and quality of life. Different methods, either definitive or fertility sparing are used for its management by using open, laparoscopic, and robotic techniques. This is a literature review presenting the role and the advantages of robotic surgery in endometriosis. Such a management is effective, safe, and feasible in hands of well-trained multidisciplinary teams even for severe cases of endometriosis.